Effect of Propolis on Inhibiting the Proliferation and Migration of T47D Breast Cancer Cell Lines - Oeij Anindita Adhika; Adelina Khristiani Rahayu; Timothy Jonathan; Julia Windi Gunadi (Global Medical & Health Communication (GMHC), 2025)
In Indonesia, breast cancer was the cancer with the highest number of cases in 2020, reaching 16.6% of all cancer cases and ranking first among all types of cancer in women. Standard cancer treatments were reported to have side effects on patients; therefore, innovation in breast cancer treatment using natural compounds must continue to be carried out, one of which is propolis. Propolis has been reported to bind to the epidermal growth factor receptor, thereby inhibiting the migration and proliferation of cancer cells. This study aims to examine the effect of propolis treatment on the viability and migration of T47D breast cancer cell lines. This study was conducted at the Molecular Biomedical Research Laboratory, Universitas Kristen Maranatha, Bandung, from May to July 2025. Propolis was extracted using ethanol maceration. Cell cytotoxicity and viability were analyzed using the MTT assay, and migration was assessed using the scratch assay after 24 and 48 hours of treatment. We analyzed the expression levels of SRY-box transcription factor 4 (SOX4) and rho-associated coiled-coil containing protein kinase 1 (ROCK1) as markers of proliferation and migration using RT-qPCR. The propolis concentration used in this study was 40 μg/ml, and each treatment was analyzed in triplicate. Results showed that propolis exhibits high cytotoxic activity, which can inhibit the viability of T47D cell lines. The viability of T47D cell lines decreased by 72% after 24 hours of treatment and further reduced to 29.3% after 48 hours of treatment. The results also showed that the migration of T47D cell lines was inhibited (−27%) after treatment with 40 μg/ml propolis, compared to negative controls (53.3%). This study concluded that propolis treatment affected the viability and migration of the T47D breast cancer cell line.